CO at 40–80 km above Kiruna observed by the ground-based microwave radiometer KIMRA and simulated by the Whole Atmosphere Community Climate Model - C. G. Hoffmann; D. E. Kinnison; R. R. Garcia; M. Palm; J. Notholt; U. Raffalski; G. Hochschild (Atmospheric Chemistry and Physics, 2012)
This study compares CO in the Arctic stratosphere and mesosphere measured by ground-based microwave radiometry with simulations made with the Whole Atmosphere Community Climate Model driven with specified dynamical fields (SD-WACCM4) for the Arctic winters 2008/2009 and 2009/2010. CO is a tracer for polar winter middle atmosphere dynamics, hence the representation of polar dynamics in the model is examined indirectly. Measurements were taken with the KIruna Microwave RAdiometer (KIMRA). The instrument, which is located in Kiruna, Northern Sweden (67.8° N, 20.4° E), provides CO profiles between 40 and 80 km altitude. The present comparison, which is one of the first between SD-WACCM4 and measurements, is performed on the smallest space and time scales currently simulated by the model; the global model is evaluated daily at the particular model grid-point closest to Kiruna. As a guide to what can generally be expected from such a comparison, the same analysis is repeated for observations of CO from the Microwave Limb Sounder (MLS), a microwave radiometer onboard NASA's Aura satellite, which has global coverage. First, time-mean profiles of CO are compared, revealing that the profile shape of KIMRA deviates from SD-WACCM4 and MLS, especially in the upper mesosphere. SD-WACCM4 and MLS are mostly consistent throughout the range of altitude considered; however, SD-WACCM4 shows slightly lower values in the upper mesosphere. Second, the time evolution is compared for the complete time series, as well as for the slowly and rapidly evolving parts alone. Overall, the agreement among the datasets is very good and the model is almost as consistent with the measurements as the measurements are with each other. Mutual correlation coefficients of the slowly varying part of the CO time series are ≥0.9 over a wide altitude range. This demonstrates that the polar winter middle atmosphere dynamics is very well represented in SD-WACCM4 and that the relaxation to analyzed meteorological fields below 50 km constrains the behavior of ...